Singapore-US Relations 2004-2024: From the Perspective of International Relations Theories - TRUONG HUE (Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pasundan, 2026)
The relationship between small states and major powers within an asymmetric, anarchic international system is shaped by power disparities that constrain the autonomy of smaller nations. This study addresses the structural vulnerabilities Singapore faces in sustaining strategic autonomy amid escalating US-China rivalry in Southeast Asia. The central research question is: how did Singapore calibrate its foreign policy toward the United States between 2004 and 2024 to secure its core national interests without becoming locked into rigid alignment? Using a qualitative-descriptive method, the study conducts a content analysis of official policy documents, diplomatic statements, and international reports. The analytical framework draws on analytical eclecticism, integrating Realism (hedging), Liberalism (economic interdependence), and Constructivism (identity and the rules-based order). The findings show that Singapore has run an adaptive dual-hedging strategy: through Realism, it secured defense cooperation with the US to offset regional uncertainty; through Liberalism, it deepened trade interdependence and multilateral engagement via ASEAN; and through Constructivism, the bilateral partnership is reinforced by a shared commitment to a rules-based order. The contribution of this study is to strengthen the small-state foreign policy literature by giving empirical support to analytical eclecticism, showing that small-state responses to major powers form a dynamic, multidimensional calculus rather than a single determined path.Keywords: Singapore, United States, International Relations Theories, Small States, Dual Hedging.